Effects of hybridized synthetic fibers on the shear properties of cement composites - Sheikh Mohd Iqbal S Zainal Abidin; Farzad Hejazi; Farah N. A. Abd. Aziz; Mohd Saleh Jaafar (MDPI, 2020)
The use of fibers in cementitious composites yields numerous benefits due to their fiber-bridging capabilities in resisting cracks. Therefore, this study aimed to improve the shear-resisting capabilities of conventional concrete through the hybridization of multiple synthetic fibers, specifically on reinforced concrete structures in seismic-prone regions. For this study, 16 hybrid fiber-reinforced concretes (HyFRC) were developed from the different combinations of Ferro macro-synthetic fibers with the Ultra-Net, Super-Net, Econo-Net, and Nylo-Mono microfibers. These hybrids were tested under direct shear, resulting in improved shear strength of controlled specimens by Ferro-Ultra (32%), Ferro-Super (24%), Ferro-Econo (44%), and Ferro-Nylo (24%). Shear energy was further assessed to comprehend the effectiveness of the fiber interactions according to the mechanical properties, dosage, bonding power, manufactured material, and form of fibers. Conclusively, all fiber combinations used in this study produced positive synergistic effects under direct shear at large crack deformations.